Utilization of hiv post exposure prophylaxis by home based caregivers in selected parts of zambia - Kayumba, Mercy; Muteka, Serah; Namusokwe, Asha.; Nkonde, Priscilla (Lusaka: University of Zambia , School of Medicine, 2014)
The purpose of this research was to ascertain the prevailing situation and some of the problems that affect utilization, knowledge and stigma that home based care givers have towards HIV post exposure prophylaxis. This was done in order to find solutions that will ensureimproved utilization of HIV post exposure prophylaxis thereby preventing new infections by care givers.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: HIV Infections--therapy.; HIV Infections--prevention & control